FT-IR spectroscopy and multivariate analysis as an auxiliary tool for diagnosis of mental disorders: Bipolar and schizophrenia cases - Arslan, M.; Ünsalan, Ozan; Araujo-Andrade, C.; Kurt, Ethan; Karatepe, Hasan Turan; Yılmaz, Ayberk; Bölükbaşı Yalçınkaya, Olcay; Herken, Hasan; ILDIZ, GÜLCE ÖĞRÜÇ (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2016)
In this study, a methodology based on Fourier-transform infrared spectroscopy and principal component analysis and partial least square methods is proposed for the analysis of blood plasma samples in order to identify spectral changes correlated with some biomarkers associated with schizophrenia and bipolarity. Our main goal was to use the spectral information for the calibration of statistical models to discriminate and classify blood plasma samples belonging to bipolar and schizophrenic patients. IR spectra of 30 samples of blood plasma obtained from each, bipolar and schizophrenic patients and healthy control group were collected. The results obtained from principal component analysis (PCA) show a clear discrimination between the bipolar (BP), schizophrenic (SZ) and control group' (CG) blood samples that also give possibility to identify three main regions that show the major differences correlated with both mental disorders (biomarkers). Furthermore, a model for the classification of the blood samples was calibrated using partial least square discriminant analysis (PLS-DA), allowing the correct classification of BP, SZ and CG samples. The results obtained applying this methodology suggest that it can be used as a complimentary diagnostic tool for the detection and discrimination of these mental diseases. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: FT-IR; Bipolar; Schizophrenia; Blood plasma; PCA; PLS; Least-Squares Regression; Infrared-Spectroscopy; Chemometrics